2022
DOI: 10.3390/cancers14225606
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Relaxometry Metrics for Brain Metastases Compared to Normal Tissues: A Pilot MR Fingerprinting Study

Abstract: The purpose of the present pilot study was to estimate T1 and T2 metric values derived simultaneously from a new, rapid Magnetic Resonance Fingerprinting (MRF) technique, as well as to assess their ability to characterize—brain metastases (BM) and normal-appearing brain tissues. Fourteen patients with BM underwent MRI, including prototype MRF, on a 3T scanner. In total, 108 measurements were analyzed: 42 from solid parts of BM’s (21 each on T1 and T2 maps) and 66 from normal-appearing brain tissue (11 ROIs eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Of note, in both the study by de Blank et al 42 and Konar et al, 43 there was no significant difference found between treated and untreated lesions, possibly due to small sample size, and this remains to be explored. 42,43 Efforts have also been made to differentiate grade and subtypes of gliomas using MRF. Radiomic analysis of 2D MRF and 3D MRF has demonstrated features helpful for glioma grade differentiation, [44][45][46] and MRF radiomics have also shown utility in prediction of IDH1 mutations.…”
Section: Technical Overviewmentioning
confidence: 82%
See 2 more Smart Citations
“…Of note, in both the study by de Blank et al 42 and Konar et al, 43 there was no significant difference found between treated and untreated lesions, possibly due to small sample size, and this remains to be explored. 42,43 Efforts have also been made to differentiate grade and subtypes of gliomas using MRF. Radiomic analysis of 2D MRF and 3D MRF has demonstrated features helpful for glioma grade differentiation, [44][45][46] and MRF radiomics have also shown utility in prediction of IDH1 mutations.…”
Section: Technical Overviewmentioning
confidence: 82%
“…In a similar study of 23 children and young adults by de Blank et al, 42 high-grade gliomas had significantly higher T1 and T2 compared with low-grade gliomas (T1: 1863 ± 70 milliseconds vs 1355 ± 187 milliseconds, P = 0.007; T2: 90 ± 13 milliseconds vs 56 ± 19 milliseconds, P = 0.013), and peritumoral white matter around low-grade gliomas had significantly lower T1 than peritumoral white matter around high-grade gliomas (T1: 1154 ± 253 milliseconds vs 1581 ± 476 milliseconds, P = 0.039). In a study by Konar et al, 43 both treated and untreated brain metastases showed higher T1 and T2 values than normal brain structures. Of note, in both the study by de Blank et al 42 and Konar et al, 43 there was no significant difference found between treated and untreated lesions, possibly due to small sample size, and this remains to be explored 42,43 …”
Section: Current Clinical Applicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…QAMPER is currently available through a material transfer agreement (MTA) with our center. Our group has experience with MR Fingerprinting (MRF) (refs: phantom, brain metastases [57,58]), which provides simultaneous T 1 and T 2 relaxometry measures in a clinically feasible amount of time. We plan to include the MRF reconstruction algorithm in our next implementation of the QAMPER platform.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been particularly challenging in vitro when small volume samples are required due to the high cost of materials or with the goal of more representative translation to ex vivo/in vivo settings 34,35 . The ISMRM/NIST MRI phantom was successfully developed for clinical applications but requires a sample size that is too large to be suitable for small animal preclinical systems 60 . Thus, there remains a need for a testbed to image small volume samples in preclinical scanners.…”
Section: Introductionmentioning
confidence: 99%